2019
DOI: 10.1111/ajpy.12226
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and experiences of targeted parents of parental alienation from their own perspective: A systematic literature review

Abstract: Objective: The aims of this systematic literature review were to identify and synthesise all relevant information about targeted parents' characteristics and experiences from their own perspective. Method: The academic databases Web of Science, PsycINFO, PubMed, EMBASE-ELSEVIER, The Cochrane Central Register of Controlled Trials, and conference abstracts were systematically searched from their inception until May 2018. The systematic review followed the preferred reporting items for systematic reviews and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 30 publications
2
22
0
4
Order By: Relevance
“…The influence of a manipulative parent who encourages the child to turn against the other parent without a valid reason can result in parental alienation that manifests as the child's refusal of the other (targeted) parent and siding with the manipulative parent (50,51). Symptoms that indicate parental alienation are constant disparaging of the other (targeted) parent, rationalization for the rejection of the other (targeted) parent, insistence on part of the child that the rejection stems from their own thoughts (the so-called independent thinker phenomenon), lack of guilt for behavior towards the targeted parent, presence of false or distorted descriptions of events that include the targeted parent (so-called borrowed scenarios), and attempts to influence the opinions of others on the targeted parent (51,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of a manipulative parent who encourages the child to turn against the other parent without a valid reason can result in parental alienation that manifests as the child's refusal of the other (targeted) parent and siding with the manipulative parent (50,51). Symptoms that indicate parental alienation are constant disparaging of the other (targeted) parent, rationalization for the rejection of the other (targeted) parent, insistence on part of the child that the rejection stems from their own thoughts (the so-called independent thinker phenomenon), lack of guilt for behavior towards the targeted parent, presence of false or distorted descriptions of events that include the targeted parent (so-called borrowed scenarios), and attempts to influence the opinions of others on the targeted parent (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…fenomen neovisnog mislioca), nedostatak osjećaja krivnje zbog postupanja prema ciljanom roditelju, postojanje lažnih ili iskrivljenih opisa događaja koji uključuju ciljanog roditelja (tzv. posuđeni scenarij) i pokušaji utjecanja na stavove drugih o ciljanom roditelju (51,52).…”
Section: Discussionunclassified
“…Nevertheless, despite feelings of despair, frustration and isolation, targeted parents appear to be resilient and seek out coping strategies (Maturana et al 2018). Coping strategies refer to how people respond to stressful events in order to minimize the perceived threat and reduce stress.…”
Section: Targeted Parents' Individual and Family Characteristicsmentioning
confidence: 99%
“…When a situation of parental alienation occurs, it is common for targeted parents to seek the help of mental health and legal professionals (Baker 2010). A recent systematic review found that targeted parents were dissatisfied with these types of formal support (Maturana et al 2018). Individuals who self-identified as targeted parents reported dissatisfaction with most of their attorneys and identified suffering with anxiety and depression during the legal proceedings involving a legal episode regarding visitation, access to the child, custody decision or parenting time, and also high levels of dissatisfaction with the final decision (Baker 2010).…”
Section: Targeted Parents and The Wider Systemsmentioning
confidence: 99%
See 1 more Smart Citation